2017
DOI: 10.1038/s41598-017-08474-0
|View full text |Cite
|
Sign up to set email alerts
|

Inhibin-A and Decorin Secreted by Human Adult Renal Stem/Progenitor Cells Through the TLR2 Engagement Induce Renal Tubular Cell Regeneration

Abstract: Acute kidney injury (AKI) is a public health problem worldwide. Several therapeutic strategies have been made to accelerate recovery and improve renal survival. Recent studies have shown that human adult renal progenitor cells (ARPCs) participate in kidney repair processes, and may be used as a possible treatment to promote regeneration in acute kidney injury. Here, we show that human tubular ARPCs (tARPCs) protect physically injured or chemically damaged renal proximal tubular epithelial cells (RPTECs) by pre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
48
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(49 citation statements)
references
References 47 publications
1
48
0
Order By: Relevance
“…Among the several disorders encountered in sepsis, AKI is the major complication and is mainly characterized by dysfunction of ECs that acquire a myofibroblast phenotype by EndMT, contributing to the renal fibrosis (26)(27)(28). Here, we investigated the effects of ARPCs on endothelial dysfunction, and for the first time we found that ARPCs, in addition to their ability to repair damaged renal tubular cells (18) and regenerate renal tubules and glomeruli (23), can also revert the sepsis-induced EndMT process that contributes to the accumulation of activated fibroblasts and myofibroblasts in kidney fibrosis (29)(30)(31)(32). In fact, following LPS stimulation, ARPCs restored constitutive endothelial and dysfunctional fibroblastic CD31, VE-cadherin, collagen I, and vimentin markers to basal levels.…”
Section: Discussionmentioning
confidence: 97%
See 3 more Smart Citations
“…Among the several disorders encountered in sepsis, AKI is the major complication and is mainly characterized by dysfunction of ECs that acquire a myofibroblast phenotype by EndMT, contributing to the renal fibrosis (26)(27)(28). Here, we investigated the effects of ARPCs on endothelial dysfunction, and for the first time we found that ARPCs, in addition to their ability to repair damaged renal tubular cells (18) and regenerate renal tubules and glomeruli (23), can also revert the sepsis-induced EndMT process that contributes to the accumulation of activated fibroblasts and myofibroblasts in kidney fibrosis (29)(30)(31)(32). In fact, following LPS stimulation, ARPCs restored constitutive endothelial and dysfunctional fibroblastic CD31, VE-cadherin, collagen I, and vimentin markers to basal levels.…”
Section: Discussionmentioning
confidence: 97%
“…Therefore, once again, ARPCs proved to be capable of producing a precise positive effect through a paracrine mechanism. Additionally, the secreted molecules are different and specific for a particular damage setting; in the case of physical or chemical damage on RPTECs, renal progenitors secreted regenerative molecules such as inhibin-A and decorin (18), whereas in the case of a septic shock, they secreted CXCL6, SAA4, and BPIFA2. The last chemokines belong to an antimicrobial peptide family that attenuates local inflammatory response and decreases the systemic toxicity of endotoxins (33).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Gaspar et al showed that pharmacological blockade of Toll-like receptor 4 (TLR-4) signaling and its downstream signaling contributors (IRAK1/4, ERK, JNK and p38 MAP kinases) abolished the cytoprotective effect of exogenously administered recombinant biglycan core protein against SI/R injury [6]. In another study, decorin secreted by human adult renal stem cells through the TLR-2 receptor induce renal tubular cell regeneration [27].…”
Section: Discussionmentioning
confidence: 99%